2019
DOI: 10.1039/c9nh00422j
|View full text |Cite
|
Sign up to set email alerts
|

Growth of extended DNTT fibers on metal substrates by suppression of step-induced nucleation

Abstract: Defect mediated nucleation upon organic film growth is effectively suppressed by initial oxygen saturating of surface steps yielding extended and epitaxially aligned crystalline fibers, that are of interest for optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…44,45 A possible reason for a broad distribution of fibre orientations could be the influence of surface defects such as step edges or kinks, which can cause parasitic nucleation and lead to deviant fibre growth, as shown before for the case of DNTT-fibres on Ag(111). 21 In that case, it was found that a step edge mediated growth could be efficiently suppressed by first exposing the sample to oxygen, which adsorbs preferentially at step edges 46,47 and thereby suppresses this specific nucleation. In general, steps on metal surfaces are chemically active sites that have greater binding energies of adsorbates and also show increased catalytic activity, which is used in heterogeneous surface reactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…44,45 A possible reason for a broad distribution of fibre orientations could be the influence of surface defects such as step edges or kinks, which can cause parasitic nucleation and lead to deviant fibre growth, as shown before for the case of DNTT-fibres on Ag(111). 21 In that case, it was found that a step edge mediated growth could be efficiently suppressed by first exposing the sample to oxygen, which adsorbs preferentially at step edges 46,47 and thereby suppresses this specific nucleation. In general, steps on metal surfaces are chemically active sites that have greater binding energies of adsorbates and also show increased catalytic activity, which is used in heterogeneous surface reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The present results further validate a strategy that had been introduced before to control the oriented growth of DNTT fibres on silver substrates. 21 While the present approach of using oxygen to decorate and thereby passivate surface steps is not directly applicable to the more inert gold surfaces, it requires more appropriate molecules. However, this might be achieved by using molecules such as fullerenes, 1,4diisocyanobenzene or 4,4 0 -biphenyl dicarboxylic acid, which in the case of low doses initially nucleate at steps 55,57,58 and thereby saturate them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Step edges are known as active sites for surface reactions and nucleation processes and often lead to step decorations. [40][41][42][43] A closer analysis of the AFM images clearly reveals a larger roughness on the (111) terasses compared to clean substrates, thus indicating that the formation of organometallic complexes is not limited to step edges. In contrast, AFM images recorded after immediate thermal desorption of the non-reacted F 6 TCNNQ species indeed reveal flat terraces next to decorated step edges (see Supporting Information).…”
Section: Influence Of Surface Roughness On Interface Reactionsmentioning
confidence: 98%